Damage evaluation of square steel tubes at material and component levels based on a cyclic loading experiment - Gui-bo Nie (Advances in Mechanical Engineering, 2018)
Circular and square steel tubes are two of the most commonly used members in the construction industry in China. Material damage and its accumulation cannot be neglected when structures undergo obvious deformation and material plasticity during severe earthquakes. In another published paper, a material damage constitutive model for Q235 steel was derived, and some of its parameters were defined based on a cyclic test. This article focuses on developing a normalized constitutive model at the material level and a damage model at the component level for square steel tubes based on experimentally derived results. First, the material damage behavior of 10 square steel tubes under five cyclic load schemes was investigated. The material damage and its accumulation at the material level were defined using a user-defined material sub-routine (UMAT) in the finite element software Abaqus. Next, the parameters in the constitutive model were calibrated by the fitting degree between the test result and numerical result. Furthermore, based on the experimental and numerical data, a damage model combined with deformation and energy was developed at the component level to evaluate the overall damage behavior of the specimens. Finally, the parameters in the damage model were calibrated based on the responses of the specimens at the time of collapse. The effect of material damage behavior and the accumulation of damage were found to significantly reduce the collapse load of specimens, which must be considered in the theoretical analysis and design process. The constitutive model and damage model developed in this article can be used to quantify the degree of damage of the material and components of structures under earthquake loads.